Enhanced biogas production from agro wastes by co-digestion with crude glycerol - Siti Kartom Kamarudin,; Anitha Muniandy,; Noor Shahirah Shamsu,; Noorhisham Tan Kofli, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Excessive of agro wastes and crude glycerol required efficient management in order to avoid environmental pollution. Varieties of elements content in agro wastes and crude glycerol highly potential to become feedstock for production of biogas. The objective of this study was to investigate the improvement of biogas production by anaerobic co-digestion of agro wastes with crude glycerol. Sugarcane bagasse, dried leaves, corn stover, cattle manure and crude glycerol were used in production of biogas using anaerobic co-digestion method conducted at room temperature, pH 6.8-7.2 for 30 days in 2L of bio-reactor. The contain of crude glycerol was determined by Gas Chromatography Mass Spectrometer (GC-MS) while the present of bio-methane was analysed by Gas Chromatography Thermal Conductively Detector (GC-TCD). Meanwhile the bio-ethanol formed was detected by High Performance Liquid Chromatography (HPLC). Mixture of cattle manure, sugarcane bagasse, and crude glycerol content of highest C/N ratio (22.42) while co-digestion of these samples produced 20L biogas g-1 VS added. Meanwhile about 33.07% to 42.27% COD removal obtained in Experiment 1 while 27.86% to 45.52% COD removal obtained in Experiment 2. Co-digestion of cattle manure and sugarcane bagasse with crude glycerol produced 3.2 L biogas g-1 VS added. About 0.28 mg/L of acetic acids detected at day 20 in Experiment 1 while 0.28 mg/L of acetic acids detected in day 15 in Experiment 2. Therefore, this study proof that the co-digestion of cattle manure, agricultural wastes and crude glycerol resulted in higher biogas yields.